Pengembangan otomasi perpustakaan Universitas Islam Negeri Sumatera Utara Medan berbasis (RADIO FREQUENCY IDENTIFICATION) - triana santi (UIN Sumatera Utara, 2019)
This paper describes the development of RFID-based Medan North Sumatra State University (UINSU) library. The development of RFID in the UINSU library is part of an effort in making efforts to increase libraries to become effective and efficient libraries in the education process. RFID is a technology that is very useful and has strengths and strengths or also called